Stationary points of lower semicontinuous multifunctions - Bancha Panyanak (2020)
© 2020, Springer Nature Switzerland AG. We guarantee the existence of stationary points for semicompact lower semicontinuous multifunctions in metric spaces. We also show that the semicompactness condition can be replaced by some other properties. Several examples illustrating the main results are also given.